X-ray study of structural changes in “di-(2-ethylhexyl) sulfosuccinic acid (AOT) /n-heptane-water” liquid crystalline system depending on the concentration of components - Sargsyan, A G; Grigoryan, S M (Journal of physics. Conference series, 2023)
Structural changes in the “sodium salt of di-(2-ethylhexyl)sulfosuccinic acid (AOT) - n-heptane-water” liquid-crystalline system depending on the AOT concentration in the n-heptane-water mixed solvent were studied using the X-ray diffraction method. The studies were carried out in a wide range of the AOT concentrations from 27 to 92% in a mixed solvent n-heptane/water=5.8 ratio.The mesomorphism of a liquid-crystalline system is on the concentration of the system. It is confirmed that at concentrations the AOT above 50%, a liquid crystal structure with an intradomain "flat" liquid crystal layered phase takes place. A “flat” lamellar lyotropic-liquid-crystalline phase with an intradomain lamellar structure is formed in the system. The structural parameters, the compactness of the liquid crystal system, the thickness of the formed layers, the surface area per molecular head on the surface of the layers depending on the concentration and thickness of the bound water layer are revealed. The liquid crystal system under study can serve as a model for studying various problems of biological membranes.